2015
DOI: 10.1021/acs.est.5b01866
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation and Stability of Reduced Graphene Oxide: Complex Roles of Divalent Cations, pH, and Natural Organic Matter

Abstract: The aggregation and stability of graphene oxide (GO) and three successively reduced GO (rGO) nanomaterials were investigated. Reduced GO species were partially reduced GO (rGO-1h), intermediately reduced GO (rGO-2h), and fully reduced GO (rGO-5h). Specifically, influence of pH, ionic strength, ion valence, and presence of natural organic matter (NOM) were studied. Results show that stability of GO in water decreases with successive reduction of functional groups, with pH having the greatest influence on rGO st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
113
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 242 publications
(131 citation statements)
references
References 37 publications
(59 reference statements)
9
113
0
4
Order By: Relevance
“…This mechanism has been posited in earlier aggregation and deposition studies where functionalized MWCNT (Yi and Chen, 2011) exhibited greater deposition than the unfunctionalized species in CaCl 2 but not NaCl systems. A recent study with variably oxidized forms of graphene also observed that in the presence NOM and divalent cations (Ca 2+ , Mg 2+ ), highly oxidized graphene rapidly aggregated due to functional group bridging with NOM and divalent ions, but less highly oxidized graphene remained suspended due lower functional group concentration and resultant reduced NOM-divalent cation bridging (Chowdhury et al, 2015). As observed in these earlier studies and the work presented here, ion valence clearly plays an important role in both nanoparticle deposition and release beyond classic charge shielding.…”
Section: Heteroaggregation Reversibility With Reduced Ionic Strengthmentioning
confidence: 94%
“…This mechanism has been posited in earlier aggregation and deposition studies where functionalized MWCNT (Yi and Chen, 2011) exhibited greater deposition than the unfunctionalized species in CaCl 2 but not NaCl systems. A recent study with variably oxidized forms of graphene also observed that in the presence NOM and divalent cations (Ca 2+ , Mg 2+ ), highly oxidized graphene rapidly aggregated due to functional group bridging with NOM and divalent ions, but less highly oxidized graphene remained suspended due lower functional group concentration and resultant reduced NOM-divalent cation bridging (Chowdhury et al, 2015). As observed in these earlier studies and the work presented here, ion valence clearly plays an important role in both nanoparticle deposition and release beyond classic charge shielding.…”
Section: Heteroaggregation Reversibility With Reduced Ionic Strengthmentioning
confidence: 94%
“…In opposition to pretreatment, where no literature dealing with wastewater exists, three papers have been found that contain data on the sedimentation behaviour of GFNs suspended in sewage: those by Chowdhury et al [40], and Ren et al [31] for GO and that by Chowdhury et al [41] for RGO.…”
Section: Primary Treatmentmentioning
confidence: 99%
“…The anion associated to the cation also interacts with the nanoflake, making the GFN more negatively charged, but it seems that, when the electrolyte concentration increases, cations have a more pronounced effect on the suspension behaviour than anions do [31]. Regarding NOM, GFNs readily adsorb it on those areas of the basal plane without oxygenated groups via hydrophobic interactions or π -π bonding [12], and two opposing processes could happen: better aggregation (because organic matter is negatively charged, and provided more binding sites for cations) or steric hindrance (due to the size of the adsorbed organic molecules, which hampers the aggregation of the nanosheets), but the second one is the predominant in simple solutions [24,35,37,40,41]. Furthermore, adsorption of organic matter might cover the oxygen-containing groups of GO, obstructing the reduction process [35].…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…The basic principle of Turbiscan is to measure both transmittance and backscatter of near-infrared pulsed light (λ = 880 nm) from the bottom to the neck of a container containing the suspension [59,60]. The physical principle of Turbiscan is based on the Lambert-Beer theory, as shown in formula (1)- (2).…”
Section: Turbiscan Tower For Aggregation Analysismentioning
confidence: 99%